1989
DOI: 10.1182/blood.v74.3.1144.bloodjournal7431144
|View full text |Cite
|
Sign up to set email alerts
|

Improved hematopoiesis in anemic Sl/Sld mice by splenectomy and therapeutic transplantation of a hematopoietic microenvironment

Abstract: The ability of a clonal hematopoiesis-supportive bone-marrow stromal cell line GBlneor to engraft and alter the microenvironment-induced anemia of Sl/Sld mice was studied. Prior to stromal cell transplantation, Sl/Sld mice received 1 Gy total body irradiation (TBI) and 13 Gy to the right hind limb. Two months after intravenous (IV) injection of 5 x 10(5) GBlneor cells, 54.4% +/- 17.0% donor origin (G418r) colony-forming cells were recovered from the right hind limb of Sl/Sld mice. Long-term bone marrow culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Several studies suggest that stromal cells in the bone marrow have immune‐modulatory effects that enhance HSC engraftment, induce donor‐specific tolerance and have a positive effect on autoimmune disorders in experimental animal models [29–32]. Human stromal cells also enhance long‐term haematopoietic engraftment after in utero transplantation in sheep [33].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that stromal cells in the bone marrow have immune‐modulatory effects that enhance HSC engraftment, induce donor‐specific tolerance and have a positive effect on autoimmune disorders in experimental animal models [29–32]. Human stromal cells also enhance long‐term haematopoietic engraftment after in utero transplantation in sheep [33].…”
Section: Discussionmentioning
confidence: 99%
“…Sl d encodes a biologically active secreted soluble SCF but lacks the membrane isoform due to an intragenic deletion of the transmembrane domain. Because the phenotype of Sl/Sl d mice revealed very severe deficiencies like reduced stem cell numbers and anemia (McCulloch et al, 1965;Anklesaria et al, 1989), the membrane form of SCF appears to be critical for normal function.…”
mentioning
confidence: 99%
“…It may be assumed that in certain cases the transplanted marrow cells encounter a defective microenvironment. In murine models, Anklesaria et al had reported on improved hematopoiesis in irradiated mice and in anemic S 1/S Id mice as a result of transplantation and engraftment of a bone marrow stromal cell line (45,46). This fact emphasizes the importance of stromal elements in the correction of decreased or defective hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%